Studi Komparatif Hukum Pendaftaran Tahah Pra dan Pasca Undang-Undang Cipta Kerja - Saleh, Sri Rahayu Muh.; Septiani, Elya; Atiqah, Nisrina (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
The mandate of Article 142 and Article 185 letter b of Omnibuslaw, was issued by Government Regulation Number 18 of 2021 concerning Management Rights, Land Rights, Flats and Land Registration (PP No. 18/2021) on February 2 2021 and ATR/ BPN No. 1 of 2021 concerning Electronic Certificates. This research will discuss land registration arrangements pre and post the Job Creation Law and then examine these arrangements using Gustav Radbuch's theory of basic legal objectives, namely (1) Legal Justice; (2) Legal Benefits; (3). Legal certainty. The author uses normative juridical research methods which include research on legal principles, legal systematics, levels of vertical and horizontal synchronization, comparison and legal history. The research results show that before the enactment of the Job Creation Law, land registration was often considered bureaucratic, slow, not transparent, impractical, to the point that registration costs were considered relatively high, whereas after the Job Creation Law, the land registration system was more computerized and digitally documented. It is hoped that there will be an increase in the digital skills of the community as well as an increase in BPN's readiness to provide online land registration services, for example by increasing the capacity of human resources and infrastructure.